Spatial-temporal differentiation characteristics of the coupling of urban resilience and green development efficiency in resource-based cities - Zhang, Saiyin; Wang, Qixiang; Yuan, Jiaxin; Wang, Jinwei (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2024)
Journal of Zhejiang University (Science Edition),2024,51(6):753⁃768 Abstract: Yellow River Basin is an important industrial belt for energy development in China with a large number of resource-based cities. However, due to the large-scale energy development and coal mining, Yellow River Basin has encountered the problems of fragile ecological environment, unreasonable resource allocation and low development quality. Nowadays, urban resilience construction and green development have become an important direction for transformation and development of resource-based cities in Yellow River Basin as the research object, this paper constructs the coupling mechanism between urban resilience and green development efficiency, and quantitatively measured the spatio-temporal pattern of coupling coordination between resilience and green development efficiency of 40 resource-based cities from 2010 to 2019 by using the physical coupling model. Based on the stochastic effects panel Tobit model, the coupling factors of resilience and green development efficiency of resource-based cities in Yellow River Basin are studied. The results show that: (1) The resilience construction of resource-based cities in Yellow River Basin has achieved remarkable progress with a steady growth trend. The green development efficiency reveals a "W" shaped fluctuation growth trend over time, and the overall growth efficiency is not significant. (2) The mean value of the system coupling degree between them fluctuates within the range of [0.7, 0.8], presenting a high coupling relationship. In addition, the degree of coupling coordination shows a trend of steady improvement over time. (3) The spatial heterogeneity of urban resilience, green development efficiency, and their coupling degree and coupling coordination degree are consistent, that is, resource-based cities in the middle and lower reaches are stronger than those in the upper reaches. (4) Government capacity, education input and population size have significant spatial differences on the impact of coupled coordinated development, while infrastructure, industrial structure and environmental regulation have spatial homogeneity. In the context of the national strategy of accelerating green transformation of resource-based cities, this study is of certain guiding significance for promoting resource-based cities to get rid of dependence on regional economic development path and high-quality development through resilience governance.